Influence of End-Stop Design Variations on Dynamic Response of Centrifugal Pendulum Vibration Absorbers - Bahadir Sarikaya; Enes Ozdemir; Murat Inalpolat; Hyun Ku Lee; Moo Suk Kim (Shock and Vibration, 2025)
Centrifugal pendulum vibration absorbers (CPVA) are passive order-tuned mechanisms with absorber masses swinging along their specific paths. Their motion is limited by end-stops preventing undesired impacts due to rotor-to-absorber and absorber-to-absorber contacts. Absorber to end-stop impacts occur especially during transient operating regimes taking place due to engine cylinder deactivation excited drivetrain resonances or at low engine speeds during vehicle take-off. End-stop placement is deemed an important design decision since it can lead to nonunison dynamic response of absorbers, increase end-stop impacts and thus hamper noise and vibration reduction capabilities of CPVA systems. This paper details an investigation into the dynamic response characteristics of impacting CPVA systems with variations of end-stop positions and compliance resulting in relevant design recommendations to minimize vibrations and noise. A generalized nonlinear dynamic model capable of simulating the torsional dynamics, absorber rocking, gravity, and end-stop compliance of CPVA systems is used. The vibration reduction and absorber amplitude ratio indices as well as the newly proposed counter torque ratio and impact ratio indices are used to benchmark the performance of CPVA systems with different absorber end-stop designs. Recommendations for the order and path of absorbers have been made to reduce the response sensitivity to end-stop positional variations, whereas the rocking rate has been identified to have an insignificant influence on the performance of impacting absorbers.